Use of fluoroquinolones and risk of rhegmatogenous retinal detachment: a retrospective cohort study using two nationwide representative claims databases - Lin, Ting-Yu; Wang, Jiun-Ling; Wang, Grace Hsin-Min; Huang, Yu-Yun; Chen, Ming-Ching; Dong, Yaa-Hui; Lo-Ciganic, Wei-Hsuan (Frontiers in Pharmacology, 2024)
BACKGROUND: While biological plausibility suggests that fluoroquinolones could lead to rhegmatogenous retinal detachment (RRD) through collagen degradation, real-world evidence on their relative risk of RRD is inconsistent, with limited information on absolute risk estimates. OBJECTIVE: To estimate the RRD risk associated with fluoroquinolones versus other antibiotics with similar indications (i.e., comparison antibiotics). METHODS: We conducted a retrospective cohort study analyzing claims data from adult patients who initiated fluoroquinolones or amoxicillin/clavulanate or ampicillin/sulbactam or extended-spectrum cephalosporins, using the Taiwan National Health Insurance Research Database (2009-2018) and the United States IBM MarketScan Database (2011-2020). Patients were followed for up to 90 days after cohort entry. For each country data, after 1:1 propensity score (PS) matching, we used Cox regression models to estimate RRD risks, presenting with hazard ratios (HR) with 95% confidence interval (95% CI). We used random-effects meta-analyses to derive pooled HRs across both counties. RESULTS: Among 24,172,032 eligible patients comprising 7,944,620 insured Taiwanese (mean age [SD], 46 [18] years; 45% male) and 16,227,412 U.S. commercially insured individuals (mean age [SD], 47 [16] years; 40% male), 10,137,468 initiated fluoroquinolones, 10,203,794 initiated amoxicillin/clavulanate or ampicillin/sulbactam, and 3,830,770 initiated extended-spectrum cephalosporins. After PS matching, similar RRD incidence rates were observed between fluoroquinolones and amoxicillin/clavulanate or ampicillin/sulbactam users (0.33 [95% CI, 0.19-0.56] versus 0.35 [95% CI, 0.26-0.46] per 1,000 person-years), yielding an HR of 0.97 (95% CI, 0.76-1.23). The RRD incidence rates were also similar comparing fluoroquinolones to extended-spectrum cephalosporins (0.36 [95% CI, 0.22-0.57] versus 0.34 [95% CI, 0.22-0.50] per 1,000 person-years; HR, 1.08 [95% CI, 0.92-1.27]). The comparative safety profiles remained consistent by country, various patient characteristic (e.g., diabetes or ophthalmic conditions), type of fluoroquinolones, follow-up duration, or treatment setting. CONCLUSIONS: This large-scale study, leveraging real-world data from Taiwan and the U.S., showed a low and comparable RRD risk among adults initiating fluoroquinolones or other antibiotics with similar indications. This suggests that the RRD risk should not deter the use of fluoroquinolone when clinically indicated.